Discriminant validity of the Structured Inventory of Malingered Symptomatology (SIMS) under conditions of simulating symptoms - Oljača, Milan; Baić , Valentina; Bugarski-Ignjatović, Vojislava (Vojnosanitetski pregled, 2023)
Background/Aim.The Structured Inventory of Malingered Symptomatology (SIMS) is a self-report measure to be used with adults, which may be utilized to assess the potential malingering of psychosis, neurologic impairment, amnesia, low intelligence, or affective disorder. The aim of the study was to examine the discriminant validity of SIMS under conditions of simulating symptoms of neurological and memory disorders, in response to a hypothetical situation, after watching a recording of an actual car accident in which a motorcycle rider sustained head injuries. Methods. The study involved 94 students (35 men and 59 women) from the University of Criminal Investigation and Police Studies in Belgrade and the Faculty of Medicine – Special Education and Rehabilitation in Novi Sad, aged 20–26 [arithmetic mean = 20.69; standard deviation (SD) = 0.80], divided into two groups (n = 47), malingerer and control. The malingerer group was instructed to identify with the motorcycle rider hit by the car and malinger symptoms related to neurological difficulties and amnesia in order to obtain greater reimbursement from the insurance company. The control group had instructions to honestly assess the probability of occurrence of the symptoms. Results. The results of the multivariate one-way analysis of variance suggested that the effect of experimental manipulation was statistically significant [F (88, 5) = 91.21, p < 0.001; η2p = 0.838]. Univariate effects were also statistically significant for all five scales. Participants in the malingerer group scored higher on all five scales than participants in the control group. The magnitudes of the effects support the largest differences between the malingerer and control groups on the scales of Memory Disorders and Neurological Disorders, which was also the basic instruction for simulating symptoms given to the participants in the malingerer group. Conclusion. The obtained results support the discriminant validity of the SIMS questionnaire in the situation of simulating symptoms of neurological disorders and memory disorders.